2011
DOI: 10.5897/jmpr11.1176
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant activity of some Morrocan hydrosols

Abstract: Essential oils are used in Cosmetic, Perfumery, Food and Pharmaceutical Industries as flavours and/or medicines. However, part of the essential oil components that remains in the distillation water (hydrosol or distillate water) has been less studied both in chemical and biological terms. This research concerns the antioxidant activity, measured through several methods, of Lavandula officinalis L., Origanum majorana L., Rosmarinus officinalis L., Salvia officinalis L. and Thymus vulgaris L., Cinnamomum verum J… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
17
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(27 citation statements)
references
References 25 publications
6
17
0
Order By: Relevance
“…For example, Salvia officinalis 0.1 g/mL had about 30% radical scavenging activity. The same concentration of Rosmarinus officinalis hydrolat had about 50% activity [31]. Our hydrolats (0.1 g/mL) had 31.43 ± 1.55% (EO1) and 27.24 ± 1.63% (EO2) antioxidant activity-the same as Salvia officinalis.…”
Section: Discussionsupporting
confidence: 49%
“…For example, Salvia officinalis 0.1 g/mL had about 30% radical scavenging activity. The same concentration of Rosmarinus officinalis hydrolat had about 50% activity [31]. Our hydrolats (0.1 g/mL) had 31.43 ± 1.55% (EO1) and 27.24 ± 1.63% (EO2) antioxidant activity-the same as Salvia officinalis.…”
Section: Discussionsupporting
confidence: 49%
“…veronense compared to the essential oil, considering the amount of thymol and carvacrol in these extracts (Table 1). Aazza et al [65] reported a similar antioxidant activity (282.6 µmol/L) for Salvia officinalis hydrosol. Quassinti et al [17] tested the antioxidant activity (DPPH) of essential oil for the species Hypericum hircinum L. subsp.…”
Section: Antioxidant Activitymentioning
confidence: 75%
“…This is the first report on the antioxidant activity of the free volatiles of Veronica species, so we cannot compare it with other results for Veronica species, but we can compare our results with other relevant EOs and hydrosols commonly used in food preservation, preservation, pharmacy and cosmetics. In comparison with reports on other plants, Aazza et al [39] investigated the ORAC activity of hydrosols of several medicinal plants (Lavandula officinalis, Origanum majorana, Rosmarinus officinalis, Salvia officinalis, Thymus vulgaris, Cinnamomum verum and Syzgium aromaticum). The hydrosol KS tested in our research has higher ORAC activity than Salvia officinalis and similar activity to Rosmarinus officinalis [39].…”
Section: Antioxidant Activitymentioning
confidence: 99%
“…In comparison with reports on other plants, Aazza et al [39] investigated the ORAC activity of hydrosols of several medicinal plants (Lavandula officinalis, Origanum majorana, Rosmarinus officinalis, Salvia officinalis, Thymus vulgaris, Cinnamomum verum and Syzgium aromaticum). The hydrosol KS tested in our research has higher ORAC activity than Salvia officinalis and similar activity to Rosmarinus officinalis [39]. Bentayeb et al [40] reported antioxidant activity for 10 EOs of the plants often used as spices.…”
Section: Antioxidant Activitymentioning
confidence: 99%